Pengaruh Intensitas Radiasi Matahari Dan Pemberian Pupuk Nitrogen Terhadap Pertumbuhan Tanaman Sawi Putih (Brassica pekinensia L. Var. Belona F1): The Influence of Solar Radiation Intensity and Nitrogen Fertilizer Application on the Growth of Cauliflower Plants (Brassica pekinensia L. Var. Belona F1) - Masyitho, Putri Dewi; Pratiwi, Sri Hariningsih; Purnamasari, Retno Tri (Journal of Applied Plant Technology, 2022)
This study aims to determine of knowing the effect of the intensity of sun radiation and the right nitrogen fertilizer on the growth of the highest chinese cabbage. The research has been carried out in Wirogunan Village, Kec. Purworejo Pasuruan City was conducted from September to December 2021. This study used a Divided Plot Design (RPT) which was repeated three times. The intensity of sun radiation is placed as the main plot (P) which consists of three levels: : 55% sun radiation intensity, : 65% sun radiation intensity, : 75% sun radiation intensity. Nitrogen fertilizer doses were placed as subplots (J) which consisted of three levels: : Nitrogen fertilizer dose 200 kg ha-1, : Nitrogen fertilizer dose 300 kg ha-1, : Nitrogen fertilizer dose of 400 kg ha-1. From the two treatments, 9 treatment combinations were obtained and each treatment was repeated three times to obtain 27 treatment combination units. The results showed that the treatment of 65% sun radiation intensity and nitrogen fertilizer 300 kg ha-1 resulted in the highest plant growth and yield. Chinese cabbage treatment with 65% sun radiation intensity and nitrogen fertilizer 300 kg ha-1 resulted in fresh weight ha-1 of 53,61 tons.